Ghost Attendance in Digital Learning: The Phenomenon of Pseudo Attendance and Academic Participation Crisis - Nur Wahyuni (Gestion Educativa, 2026)
The phenomenon of ghost attendance, or pseudo-attendance, in digital learning is a serious and increasingly prevalent issue accompanying the expansion of technology-based education. Ghost attendance occurs when students are technically registered and "present" in online learning sessions but are not actively, cognitively, or emotionally engaged in the learning process. This article systematically examines the driving factors behind ghost attendance, its impact on learning quality, and effective intervention strategies. Through a systematic literature review of 20 selected studies published between 2021 and 2024, this study identifies five key dimensions of the ghost attendance phenomenon: digital disengagement, digital literacy deficits, environmental distractions, learning design mismatches, and intrinsic motivation crises. The findings reveal that ghost attendance is not merely a technical or disciplinary issue but rather a reflection of a deeper pedagogical crisis within the digital learning ecosystem. The implications of this research include policy recommendations for redesigning digital learning strategies centered on active and authentic student engagement..